Optimal Active Control of Structures Using a Screw Jack Device and Open-Loop Linear Quadratic Gaussian Controller - Noormohamed, Ali; Mercan, Oya; Ashasi-Sorkhabi, Ali (Frontiers in Built Environment, 2019)
A screw jack is a device which converts input torque into amplified axial force, capitalizing on the device’s gearbox mechanism. Traditionally used in auto repair shops, the screw jack has been studied for the first time for active structural control. The dynamic properties of the device were investigated using open loop control, and the screw jack was found to have a high delay between command and measured force. Numerical simulations and parametric studies of SDOF systems with an LQG-controlled screw jack showed improvements to structural performance at 4 different levels of control effort. Loop simulation method experiments were conducted under seven ground motion records – benefits to structural response were dependent on the type of earthquake, with greater benefits observed for records with greater low-frequency content. Future work should investigate the types of structures and earthquakes for which the screw jack is most impactful using real-time hybrid simulation.